Kandungan protein kasar dan serat kasar, sert kasar mineral ca hijauan padang pengembalaan pada musim kemarau di desa kambata wundut kabupaten sumba timur - Ederson Sakti Maramba Awang; Dominggus B. Osa; Stefanus Tani Temu (Jurnal Peternakan Lahan Kering, 2019)
The study was carried out for 2 months on the grassland in Kambata Wundut Village district Lewa Sumba Timur regency. The study aimed at evaluating crude protein (CP), crude fiber (CF), and Ca content of native grassland in dry season. Survey method and on the field evaluation using 1m x1m square frame. Collected data were analyzed to calculate the available CP, CF, and Ca content. The result found that the available CP, CF, and Ca respectively were 8,30%, 31,18%, 0,69%.